An analytic observational study on complaints management in the general practice out of hours care setting: who complains, why, and what can we do about it?. Issue 1 (December 2016) - Barragry, Ruth A.; Varadkar, Leo E.; Hanlon, David K.; Bailey, Ken F.; O'Dowd, Tom C.; O'Shea, Brendan J.
Abstract Background General Practice Co-Operatives provide most out of hours care in communities in Ireland. Limited data exists on patient complaints. This study reports on complaints at Kildare and West Wicklow Doctors on Call ('K Doc'), a GP Co-Operative in Ireland, examining the impact of a formal risk reduction strategy implemented (2010-2013). The aim of the study was to determine if it was possible to reduce the rate of written complaints per 1000 consultations through a formal approach encompassing evaluation of complaints, improved communication in relation to complaints, and more direct use of insights gained from complaints analysis in continuing professional development at the Co-Operative. Methods Initially, complaints submitted over an 18 month period (01.06.08 to 31.12.09) were analysed. Complaint rate (number of complaints per 1000 consultations), complainant demographics, aspects of complaint response at the Co-Operative, and nature of complaint were recorded. Based on analysis, a risk reduction strategy was undertaken, including procedural change, focused training and education. Areas selected for improvement during a second phase of data collection included complaints rate, timeliness of Co-Operative response to complaint, and rate of complaint notification to patient's GP. Further analysis was then carried out over a 45 month period (01.01.10 to 30.09.13). Results From 2008-2013, 216, 716 patient consultations occurred. Complaints were received from 131 individuals, regarding 125 patients. Following introduction of risk reduction strategy, complaints rate reduced by 36 %, from 0.77 to 0.49 per 1000 consultations (p  = 0.02) between the two periods of data collection. Timeliness of response from Co-Operative to the complainant improved from 63 % to 75 %. Notification of complaint to the patient's GP improved from 48 % to 96 %. Most complaints were not associated with medically significant events. The largest categories of complaint related to clinical care (55 %n  = 69), cost (46 %, n  = 58), communication (42 %, n  = 53), and process of care (15 %, n  = 19). Mothers of affluent paediatric patients were most likely to make formal complaints. Conclusions This study reports a statistically significant reduction in complaints rate of 36 % following introduction of risk reduction strategies at a GP Co –Operative. Out of hours consulting is known to be an area of high medical risk. Findings are of interest where number and costs of complaints against GPs are elsewhere reported to be rising, contributing to medical inflation, and to public concern.